Microbial approach of epitope tagged MFE-23 single fragment antibodies production - Razmaeda Sarastry (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Antibodies have been investigated for future clinical application in cancer management. An antibody, MFE-23 scFv is known for its ability to bind Carcinoembryonic Antigen (CEA). Different from a full length antibody, single-chain variable fragments (scFvs) are recombinant antibodies in which single polypeptide is engineered to replace variable regions encoding antigen-binding domain. In vitro production of single chain fragment antibodies may use E. coli microorganism for its ability to self-replicating a plasmid. Objective: This study aimed to produce his- and myc- tagged MFE-23 scFv antibodies by using E. coli culture and to detect their solubility by using ELISA assay. Methods: Transformed E. coli containing sequences of MFE-23 coding were inoculated and evaluated for their optical density. An ELISA plate was coated by CEA or PBS and secondary antibodies were anti-his, anti-myc and anti-MFE. Horseradish peroxidase-OPD substrate was added to produce chromatic reaction for qualitative detection. Results: The results showed that each characterized tube was positive for myc-tagged MFE, his- and myc- tagged MFE, and his-tagged MFE for tube 1, 2, and 3 respectively.Conclusion: This study indicated that transformed E. coli culture is a suitable host for MFE-23 svFV production, and qualitative ELISA assay is a simple useful method for antibody detection and characterization of single chain antibodies.